Penerapan Metode Diskusi dan Project Based Learning Terhadap Motivasi Belajar Mahasiswa pada Matakuliah PAK di Universitas Terbuka di Kabupaten Mamasa, Sulawesi Barat - Iva Liliani Minanga; Wahyu Wijiati (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the influence of discussion methods and Project-Based Learning (PjBL) on students’ learning motivation in Christian Religious Education courses at Universitas Terbuka in Mamasa Regency, West Sulawesi. This research uses a quantitative correlational approach with a purposive sampling technique involving 27 students. Data collection techniques include observation, interviews, and questionnaires. The findings indicate that active learning strategies such as discussion and PjBL have the potential to improve student participation, engagement, and learning motivation in distance learning environments. The study also highlights that contextual and collaborative learning approaches are relevant to the characteristics of higher education students and can support meaningful learning experiences in Christian Religious Education.